Students’ Perception of Classroom Physical Environment In Learning English at Smpn 23 Solok Selatan - Fiti Aning Aftika; Dinovia Fannil Kher (Universitas Negeri Padang, 2023)
In teaching and learning activities, the learning environment is very important. It helps in the delivery of educational activities. Especially when teaching English. Students who study English must stay focused because it is a foreign language for Indonesians. The purpose of this study was to determine students' perceptions of the physical environment in the classroom. The subjects in this study were students of SMPN 23 Solok Selatan. The object in this study is the student's perception of various indicators. This research method is descriptive quantitative. Data collection techniques using questionnaires. The results of this study are found in five indicators, namely: the first indicator of indoor air quality obtained a positive score of 3.12. The level of achievement of the respondents was 77.98%, the second indicator of lighting obtained a positive score of 3.12. The level of achievement of the respondents was 78.17%, the three acoustic indicators obtained a positive score of 3.08. The level of achievement of the respondents was 77.14%, the four indicators of building age and quality obtained a positive score of 3.09. The level of achievement of the respondents was 77.3%, the five class size indicators obtained a positive score of 3.08. The level of achievement of respondents is 76.42%. That is, students perceive positive perceptions about the state of the physical environment in their class. The physical environment of the class is very important, to support students in learning and teachers in teaching, there must be adequate facilities. Especially in English teaching and learning subjects, considering that English is a foreign language.